PENERAPAN METODE SURVEY QUESTION READ RECITE REVIEW (SQ3R) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA DI KELAS V SDN 032 KUALU - Sihombing, Erliana Leo; Syahrilfuddin, Syahrilfuddin; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to improve learning outcomes through the application of methods SQ3R IPS Students in class V SDN 032 Kualu Pekanbaru, while the time the study was conducted in the academic year 2015/2016. Design of this research is the Classroom Action Research (PTK). As the subjects in this study is the fifth grade students of SDN 032 Kualu, with 28 students, consisting of 11 men and 17 women. Based on the analysis of data it can be concluded that the application of the method SQ3R can improve learning outcomes IPS Students in class V SDN 032 Kualu, this can be seen on the data to prove it: the teacher's activities first cycle 1 meeting obtained by percentage of 65% (good), the first cycle of meetings 2 amounted to 75% (good). In the second cycle of meeting 1 85% (very good). While on the second cycle 2 meeting obtained by percentage of 95% (very good). Student activity I cycle 1 meeting obtained by percentage of 65% (good), the first cycle 2 meeting obtained a percentage of 75% (good), with an increase of 10%. Then in the second cycle 1 meeting obtained by percentage of 90% (very good), and the second cycle 2 meeting obtained by percentage of 95% (very good). Learning outcome from a base score of 62.82 increased in the first cycle with the average being 69.64 compared with a base score, which means the increase of 6.82 (11%). In the second cycle average of 78.57 an increase of 8.93 (13%) of the average score of the base. Mastery learning the basic score of 32% or 9 students from 28 students, increased in the first cycle of 57% or students who completed as many as 16 people and the second cycle was obtained completeness of students by 93% or as many as 26 students received grades above KKM 70.Keywords: Social Learning Outcomes, SQ3R